Legal Accountability for the Use of Artificial Intelligence in Government Administrative Decision-Making in Indonesia - Muhammad Suhardi (International Journal of Scientific Research, 2025)
This study examines the legal accountability of Artificial Intelligence (AI) use in administrative decision-making in Indonesia. The main objective is to clarify the juridical position of AI within government administration and to determine whether AI may function as an autonomous decision-maker or only as an auxiliary instrument supporting public officials. This research employs a qualitative legal method with a normative-juridical approach and a single-case study of Indonesia. Data were collected through documentary study of primary legal materials, including laws and regulations on government administration, public services, electronic-based government, electronic systems, and personal data protection, supported by relevant scholarly literature on AI accountability and public administration. The findings show that Indonesian law does not recognize AI as a holder of public authority. Administrative authority remains attached to government bodies and authorized public officials. AI may assist processes such as data verification, risk assessment, classification, and recommendation, but final decisions affecting citizens’ rights, obligations, legal status, or access to public services must remain under human legal responsibility. The study also finds that Indonesia’s regulatory framework remains fragmented and lacks specific rules on human oversight, explainability, auditability, and contestability in AI-assisted decisions. This article contributes by proposing the concept of AI-assisted administrative accountability, which places AI under legality, human authority, procedural fairness, data protection, and public accountability.